Depression Augments Activity-Related Pain in Women but not in Men with Chronic Musculoskeletal Conditions. (2008) - Adams, Heather; Thibault, Pascal; Davidson, Nicole; Simmonds, Maureen; Velly, Ana; Sullivan, Michael JL
Abstract : OBJECTIVES: The primary objective of the present study was to examine the role of sex as a moderator of the relation between depression and activity-related pain. METHODS: The study sample consisted of 83 participants (42 women, 41 men) with musculoskeletal conditions. Participants were asked to lift a series of 18 canisters that varied in weight (2.9 kg, 3.4 kg and 3.9 kg) and distance from the body. Participants were asked to rate their pain while they lifted each canister and estimate the weight of the canisters. RESULTS: Consistent with previous research, the relations among depression, pain intensity and disability were stronger for women than for men. ANOVA revealed that depression was associated with more intense activity-related pain in women only. For both women and men, the intensity of pain increased with each trial, although the weight of the objects lifted remained constant. Neither sex nor depression had an effect on participants' weight estimates. CONCLUSIONS: The present discussion addresses the mechanisms through which depression may differentially affect pain in women and men. It also addresses the potential clinical implications of pain-augmenting effects of depression in women.